Managing public service communication through cyber public relations in BBSPJI Tekstil - Farsya, Refalina Nur; Lukman, Syauqy (Universitas Padjadjaran, 2026)
Background: The implementation of e-government positions government agency websites as a medium for transparent and credible public service communication. However, previous research has mostly discussed technical aspects and user perceptions, with few studies addressing Cyber Public Relations (CPR) in technical government agencies or industries. Purpose: The research purpose is to evaluate management and information structure of public service communication using the framework of CPR on the BBSPJI Tekstil website. Methods: This research used a qualitative approach with case study design. Data were collected through interviews and observations during independent internships, toward contents and publications on BBSPJI Tekstil websites. Data analysis was performed using descriptive qualitative techniques on information structure, content management processes, and internal coordination mechanisms. Results: The findings revealed that the BBSPJI Tekstil website serves as a medium of public service communication, yet its effectiveness is limited by three factors, which are inconsistent information structures across service pages, irregular content updates that cause data differences with national SIPPN platform, and bureaucratic coordination delays among internal work units. This obstacle limits the website’s strategic role as a tool of CPR in encouraging transparency and public trust. Conclusion: The study concludes that website management in government agencies should be reframed from a technical-administration only task to a strategic CPR function that requires systematic internal communication and governance. Implications: This research contributes to the literature on e-government and Government Public Relations (GPR) by promoting internal communication in CPR practices within government institutions.